Un milieu de travail diversifié : l’apport de l’obligation d’accommodement raisonnable selon le droit international et le droit canadien - Pierre Verge; Dominic Roux (Perspectives Interdisciplinaires sur le Travail et la Santé)
“Reasonable” accommodation : human diversity in the workplace is clearly subordinate to such a practice. The issue is the right to work, borne particularly by the right to equality in its recognition and its exercise. This means that the legal system in question must prohibit discrimination in all facets of employment, and its corollary, the employer’s duty to reasonably accommodate victims of such discrimination. What place is reserved in international law and Canadian law for this obligation for reasonable accommodation ? In their respective spheres of application, they are each called on to ensure the right to equality ; they not only have to allow the possibility of diversity in the workplace, by specifically protecting it, but they also have to promote it by appropriate measures and management practices that take into account the actual situation of the workers involved. The situation of disabled workers in workplaces illustrates the problem in a specific way.